L’encadrement juridique de la conditionnalité des accords de confirmation du Fonds monétaire international - Samson, Clément (Études internationales, 1988)
The International Monetary fund agrees on stand-by agreements with a large number of countries of the world, allowing these countries to obtain substantial lines of credit. These agreements are made up of a group of conditions, where the generic term "conditionality" originates. This notion has been all the more legally formulated since the Fund's decision taken on March 2"d, 1979. The author of this article looks into each one of the 12 paragraphs and underlying principles that constitute the decision. Afterwards, the author examines paragraph 3 in detail, which enacts that these stand-by agreements are not international agreements, and analyses the reasons motivating such a decision on behalf of the Fund. The author also deals with the underlying issue of the legal type of international convention that a stand-by agreement may constitute: the "gentleman's agreement" or the unilateral mandatory declaration or the unenforceable agreement. Finally, the text ends with the review of the principal sanctions linked to the infringement of the stand-by agreement standards.